Perancangan Sistem Pendeteksi Kebakaran Berbasis IoT Menggunakan ESP-32 - Setiawan, Jimy; Warohma, Ayu Mawadda (Universitas Multi Data Palembang, 2026)
Fire is a serious threat to the home environment because it has the potential to cause material losses and casualties if not detected early. This study aims to design and implement an Internet of Things (IoT)-based fire detection system using an ESP-32 microcontroller. The system utilizes a fire sensor as an input device to detect the presence of flames and send warning notifications to users via the Telegram application in real-time. The success of the system was evaluated based on three main parameters, namely sensor detection distance, notification delivery response time, and system power consumption efficiency. Test results show that the system is capable of detecting flames at an effective distance of 10–100 cm with an average notification response time of 2–3 seconds. In addition, the concept of green computing is applied through the selection of low-power devices and the activation of output components only in emergency conditions. Based on these results, this system can be used as an effective and energy-efficient early fire warning solution for the home environment.